Effect of Dark, Hard, and Vitreous Kernel Content on Protein Molecular Weight Distribution and on Milling and Breadmaking Quality Characteristics for Hard Spring Wheat Samples from Diverse Growing Regions. Issue 6 (24th June 2015) - Baasandorj, Tsogtbayar; Ohm, Jae‐Bom; Simsek, Senay
Abstract : Kernel vitreousness is an important grading characteristic for segregation of subclasses of hard red spring (HRS) wheat in the United States. This research investigated the protein molecular weight distribution (MWD) and the flour and baking quality characteristics of different HRS wheat market subclasses. The U.S. regional crop quality survey samples obtained from six regions for three consecutive growing years were used for subclass segregation based on the dark, hard, and vitreous (DHV) kernel percentage. Flour milled from HRS wheat with greater percentages of DHV kernel showed higher water absorption capacity for breadmaking. Protein MWD parameters could be related to the association between DHV kernel level and water absorption. Specifically, flour protein fractions rich in gliadins and high‐molecular‐weight polymeric proteins in the SDS‐unextractable fraction were identified to have significant and positive correlations with both DHV kernels and flour water absorption levels. An example further showed the importance of flour water absorption on potential economic incentives that can be gained with having a greater percentage of vitreous kernels. This information could help the flour milling and baking industry to segregate the different subclasses of HRS wheat with varying DHV content for their intended end‐use applications.